Biostimulants in Plant Science - Mahyar Mirmajlessi, Seyed; Radhakrishnan, Ramalingam (IntechOpen, 2020)
Natural-based substances, 'plant biostimulants', have been considered as environmentally friendly alternatives to agrichemicals. Biostimulants may comprise microbial inoculants, humic acids, fulvic acids, seaweed extracts, etc. These biostimulants have biopesticide and biostimulant utilities. Elucidations on direct or microbially mediated functions of biostimulants are presented in this book to illustrate fundamental principles and recent applications underlying this technology. This book has encompassed a cross-section of topics on different concepts to describe effective strategies by using these substances and/or beneficial microorganisms within sustainable agroecosystems. I sincerely hope that the information provided adequately reflects the objectives of this compilation. "One of the first conditions of happiness is that the link between man and nature shall not be broken." Leo Tolstoy